2014
DOI: 10.1186/1471-230x-14-53
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of bevacizumab in elderly patients with metastatic colorectal cancer: results from the Czech population-based registry

Abstract: BackgroundPatients aged 65 years and older represent the majority of patients with metastatic colorectal cancer (mCRC). However, this patient population is often underrepresented in clinical trials and probably undertreated in the clinical practice.MethodsWe have analysed the outcomes of 3,187 mCRC patients treated with first-line bevacizumab based on data from the Czech national registry of mCRC patients aiming to compare the treatment efficacy and safety according to the age categories.ResultsIn total, 2,126… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 24 publications
4
17
0
Order By: Relevance
“…Bevacizumab-containing CTX outcomes from routine clinical practice were monitored and/or reported in mCRC patients registries such as prospective US BRiTE registry (n = 1,953) 9 or retrospective Czech (n = 3,187) and French (n = 1,322) registries. 10 , 18 These large first-line setting registries confirmed similarity of clinical benefit between younger and older patients, previously reported in randomized clinical trials and pooled analysis.…”
Section: Discussionsupporting
confidence: 82%
“…Bevacizumab-containing CTX outcomes from routine clinical practice were monitored and/or reported in mCRC patients registries such as prospective US BRiTE registry (n = 1,953) 9 or retrospective Czech (n = 3,187) and French (n = 1,322) registries. 10 , 18 These large first-line setting registries confirmed similarity of clinical benefit between younger and older patients, previously reported in randomized clinical trials and pooled analysis.…”
Section: Discussionsupporting
confidence: 82%
“…The adverse events from bevacizumab treatment observed in this study are consistent with those published in post-registrational trials, including BEAT, BRiTE and ARIES [ 11 - 13 ]. We confirmed that severe (grade 3–5) events, including arterial thromboembolic events, proteinuria, gastrointestinal perforation and wound-healing complications were rare with incidence and spectrum of adverse events comparable across all age groups [ 14 ]. Taken together, the adverse events related to bevacizumab are acceptable and well tolerated.…”
Section: Discussionsupporting
confidence: 66%
“…However, the parameters of our analysis that confer substantial reliability to the presented results are, for example, unselective multicenter input of evaluated data and the proportion of tumors with wtKRAS vs mtKRAS, mirroring the proportion of KRAS mutation previously detected in the Czech Republic during a one year survey [ 9 ]. We excluded a potential bias caused by inclusion patients with known KRAS status only, as no difference was observed between PFS of mCRC patients treated in the first-line with bevacizumab and OX- or IRI-based chemotherapy with KRAS-known (11.5 months, 95% CI 11.0-12.1) and KRAS-unknown (11.6 months, 95% CI 11.0-12.2) which is further underlined by KRAS-unselected published data on first-line bevacizumab in mCRC patients based on CORECT registry [ 14 ]. An existing limitation of the present study is that we had no data specifying the type of KRAS mutation, NRAS mutation or data on BRAF mutation.…”
Section: Discussionmentioning
confidence: 93%
“…Three studies reported the presence of primary metastases at diagnosis. The proportion of patients with the presence of synchronous metastasis ranged from 58.0 to 81.2%, and it was similar across the different age groups (Kozloff et al 2010; Slavicek et al 2014; Parakh et al 2015).…”
Section: Resultsmentioning
confidence: 82%